Assessment of lung dose from indoor 222Rn and 220Rn exposure in the Jalandhar and Kapurthala districts of Punjab, India. Issue 9 (November 2017) - Mehra, Rohit; Jakhu, Rajan; Mittal, HM
Radon ( 222 Rn) and its progenies are the main source of the inhalation dose received by humans due to natural radioactivity. Residential houses of different villages of Jalandhar and Kapurthala districts of Punjab, India, were chosen for the present study. An attempt has been made to estimate the dose to lung (DRL ) due to indoor 222 Rn concentration. The results of observed values of dose rate to lung ( D lung ), dose to tracheo-bronchial region ( D T-B ), dose to pulmonary + pulmonary lymph region ( D P+PL ), dose to lung ( D RL ) from 222 Rn exposure and dose to lung ( D TL ) from indoor Thoron ( 220 Rn) exposure along with their indoor concentration are summarized in this manuscript. The average value of the measured 222 Rn ( C R ) and 220 Rn ( C T ) concentration in air is 38 and 61 Bq m −3 . The value of D lung varies from 0.76 to 2.52 nGy h −1 . The average value of the D T-B, D P+PL and D RL is 1.82, 1.82 and 3.65 nSv, respectively. The average dose received by the lungs from 220 Rn exposure is 0.06 µSv. Since the dose in the study area is less than reference level of 10 mSv as recommended by the International Commission on Radiological Protection (ICRP), the studied area is safe from the exposure risk of indoor 222 Rn and 220 Rn.